Sébastien Plociniczak, L’Encastrement Social des Marchés. Éléments théoriques et empiriques pour une analyse en termes de réseaux relationnels - Sébastien Plociniczak (Revue de la Régulation)
Despite the core role played by market in economic theoretical frameworks, the market is still little addressed and finally remains a vague type at best equivoque. This thesis aims to contribute to a collective pattern devoted to the diversification of market analysis since the 70s. This collective pattern is the New Economic Sociology, founded and built on a central idea, i.e. the embeddedness. In the perspective of Karl Polanyi and Mark Granovetter’s works, the thesis intends thus to enlighten first the use of this idea as the necessary clarification does not occur until now. Then, it puts forward the fact that an analysis of markets may definitely benefit from a deeper understanding of the multilateral logic of relational networks. At last, on the base of main assumptions defined in this thesis, the robustness of the heuristic contractual model of the Transaction Costs Economics depicted by Oliver E. Williamson is assessed.